INNOVATIVE DEVELOPMENT OF SMALLAND MEDIUM-SCALE BUSINESS: REGIONAL ASPECT - A. Yakushev (Управленческие науки)
Regional innovation policy is aimed at the formation and development of innovative subsystem of the regional economy and at the maintenance of a sustainable regional economy’s growth. Having undeniable advantage in innovative projects implementation, small- and medium-scale enterprises is the most attractive in the process, which is confirmed by the statistical data on the effectiveness of innovative development of the Chelyabinsk region, given in the article.The article focuses on the problems faced by regional entrepreneurship in the implementation of innovative policies along with its progress.Within the economy development strategy and with regard to the problems, the article considers the existing. The article is based on the research results, carried out at the expense of budget funds on the Financial University’s state task in 2014.infrastructure of innovation activities support of small- and medium-scale enterprises in Chelyabinsk region, their place and role in the improvement of the innovation process management. It is noted that the infrastructure requires an appropriate management system, which is of particular importance in today’s economy.The article offers the organizational-economic model as an optional system of innovative development management of small- and medium-scale enterprises. In accordance with the assistance program, the model formation is based on the three phases, and structurally the model consists of two subsystems: the controlling one and the manageable one. The article considers the model structure in detail and its role in the development of the innovation system of the Chelyabinsk region.